Revision total knee arthroplasty (TKA): mid-term outcomes and bone loss/quality evaluation and treatment - Rosso, Federica (J Orthop Surg Res, 2019)
BACKGROUND: Revision total knee arthroplasty (rTKA) is a demanding procedure, with a high complication and failure rate and a high rate of bone losses and poor bone quality. Different classifications for bone losses have been proposed, but they do not consider bone quality, which may affect implant fixation. The aim of this study is to describe the outcomes of a consecutive series of rTKA. Furthermore, a modified bone loss classification will be proposed based also on bone quality. Finally, the association between radiolucent line (RLL) development and different risk factors will be evaluated. METHODS: All the patients who underwent rTKA between 2008 and 2016 in the same institution were included. rTKAs were performed by the same surgeon according to the three-step technique. Bone losses were classified according to the proposed classification, including bone quality evaluation. The Knee Scoring System (KSS), the Hospital for Special Surgery Knee Score (HSS), and the SF-12 were used for the clinical evaluation. Radiological evaluation was performed according to the Knee Society Roentgenographic Evaluation System. Different possible risk factors (i.e., gender, age, amount of bone losses) associated to RLL development were identified, and this association was evaluated using logistic regression. RESULTS: Fifty-one patients (53 knees) were included (60.8% female, average age 71.5 years). The average follow-up was 56.6 months (range 24–182). The most frequent cause of failure was aseptic loosening (41.5%). 18.9% of the cases demonstrated poor bone quality. Bone losses were treated according to the proposed algorithm. In all the cases, there was a significant improvement in all the scores (P < 0.05). The average post-operative range of motion was 110.5° (SD 10.7). At the radiological evaluation, all the implants resulted well aligned, with 15.1% of non-progressive RLL. There were 2 failures, with a cumulative survivorship of 92.1% at the last follow-up (SD 5.3%). At the logistic regression, none of the evaluated variables resulted associated to RLL development. CONCLUSION: rTKA is a demanding procedure, and adequate treatment of bone losses is mandatory to achieve good results. However, also bone quality should be taken into consideration when approaching bone losses, and the proposed classification may need surgeons after an adequate validation. LEVEL OF EVIDENCE: Level IV